Comorbidities, social, and psychological factors associated with headache in adult Indonesians: data from the 5th Indonesian Family Life Survey (IFLS-5) - Barus, Jimmy Fransisco Abadinta; Sudharta, Harvey; Suswanti, Ika; Sasmita, Poppy; Widyadharma, I Putu; Turana, Yuda (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundHeadache is a significant health problem worldwide, but national data on headaches in Indonesia are unavailable. Various risk factors have been identified as triggers or factors affecting its occurrence and severity. This study aimed to identify factors associated with headache occurrence in Indonesians aged 20 to 65 years. MethodsA cross-sectional study was conducted involving 26,263 participants aged 20 to 65 years. We covered any social, psychological, and comorbidity variables found in the fifth Indonesian Family Life Survey (IFLS) that could be linked to headaches. A multivariate-adjusted logistic regression model was used to estimate the odds ratios (ORs) and 95% confidence intervals (CI). ResultsThe prevalence of those who had headache once in the past four weeks was 62.1%. Headache was associated with sleep disturbances (OR 2.24; CI 95% 2.11 – 2.36; p<0.001), depression (OR 1.79; CI 95% 1.67-1.92; p<0.001), hypertension (OR 1.79; CI 95% 1.64 – 1.96; p<0.001), female sex (OR 1.64; CI 95% 1.55 – 1.73; p<0.001), early adulthood (OR 1.32; CI 95% 1.24 – 1.42; p<0.001), hypercholesterolemia (OR 1.33; CI 95% 1.15 – 1.52; p = 0.001), poor/moderate sleep quality (OR 1.22; CI 95% 1.15 – 1.29; p<0.001), and low income (OR 1.12; CI 95% 1.05 – 1.19; p = 0.001). ConclusionsThis study demonstrated that sleep disturbances were the dominant risk factor of headache in subjects aged 20 to 65 years. Furthermore, sleep disturbance treatment should especially be considered in patients with a high level of headache.